The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/rcm.575
|View full text |Cite
|
Sign up to set email alerts
|

Loss of isocyanic acid from the internal oxadiazole ring of protonated molecules of some 2,5‐diaryl‐1,3,4‐oxadiazoles

Abstract: The fragmentation pattern of some protonated 2,5-diaryl-1,3,4-oxadiazoles is discussed. An unusual decomposition consisting of elimination of the isocyanic acid molecule from the internal oxadiazole ring was found. This fragmentation pathway was deduced on the basis of B/E linked scan mass spectra of metastable ions with liquid secondary ion mass spectrometry as the ionization method and also of low-energy CID mass spectra where electrospray was used as the ionization technique. High resolution measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…The B/E mass spectra of protonated 1-6 molecules ([M ϩ H] ϩ ions) are shown in Figure 2. In the previous paper the fragmentation pathways of protonated molecules of 2,5-disubstituted-1,3,4-oxadiazoles were presented [17]. It was shown that these compounds lost the isocyanic acid molecule (HNCO, loss of mass 43) from the oxadiazole ring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The B/E mass spectra of protonated 1-6 molecules ([M ϩ H] ϩ ions) are shown in Figure 2. In the previous paper the fragmentation pathways of protonated molecules of 2,5-disubstituted-1,3,4-oxadiazoles were presented [17]. It was shown that these compounds lost the isocyanic acid molecule (HNCO, loss of mass 43) from the oxadiazole ring.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of [M ϩ H] ϩ ions the loss of isocyanic acid was observed and for [M [17]. In this paper the mass spectrometric fragmentation pathways of protonated 1,3,4-oxadiazoles (1-6, Scheme 1) are analyzed in more detail and compared with the fragmentation pathways observed for lithiated derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high affinity to water absorption, the wide signal at 2000-3700 cm −1 became wider and more intensive than SPPOD and SCDPPOD. The branching and degradation of diphenyl ether C-O-C bond catalyzed by acid at high temperature which lead to the phenoxy terminated segment formation has been previously reported in literatures [57,[60][61][62]. Also, at high temperatures, protonated oxadiazole groups are degraded and suffer from cleavage, analogous to the mechanism proposed by Franski et al [61].…”
Section: Polymer Synthesismentioning
confidence: 59%
“…The branching and degradation of diphenyl ether C-O-C bond catalyzed by acid at high temperature which lead to the phenoxy terminated segment formation has been previously reported in literatures [57,[60][61][62]. Also, at high temperatures, protonated oxadiazole groups are degraded and suffer from cleavage, analogous to the mechanism proposed by Franski et al [61]. This degradation produces some active groups such as amine, amide, carbonyl and others that lead to branching and some partially crosslinking in polymer structure [43,51,57,62].…”
Section: Polymer Synthesismentioning
confidence: 95%